2014
DOI: 10.4161/15548627.2014.984283
|View full text |Cite
|
Sign up to set email alerts
|

SUMO1 promotes Aβ production via the modulation of autophagy

Abstract: Autophagy is one of the main mechanisms in the pathophysiology of neurodegenerative disease. The accumulation of autophagic vacuoles (AVs) in affected neurons is responsible for amyloid-β (Aβ) production. Previously, we reported that SUMO1 (small ubiquitin-like modifier 1) increases Aβ levels. In this study, we explored the mechanisms underlying this. We investigated whether AV formation is necessary for Aβ production by SUMO1. Overexpression of SUMO1 increased autophagic activation, inducing the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 46 publications
3
47
1
1
Order By: Relevance
“…Furthermore, other UBLs have been implicated in the regulation of aggrephagy. SUMO-1 has been suggested to regulate the formation of autophagic vesicles in neurons and thus influence the production of pathogenic amyloid-b [57]. FAT10 has been shown to bind to and regulate the solubility of polyQ proteins, and localize to aggresomes upon proteasome inhibition [58,59].…”
Section: Aggrephagymentioning
confidence: 99%
“…Furthermore, other UBLs have been implicated in the regulation of aggrephagy. SUMO-1 has been suggested to regulate the formation of autophagic vesicles in neurons and thus influence the production of pathogenic amyloid-b [57]. FAT10 has been shown to bind to and regulate the solubility of polyQ proteins, and localize to aggresomes upon proteasome inhibition [58,59].…”
Section: Aggrephagymentioning
confidence: 99%
“…Autophagy receptors and Lys-63 poly-Ub chains are essential for aggrephagy, and their activity is maintained also by other Ub-related molecules. The ubiquitin-like proteins SUMO-1 and FAT10 bind and contribute to the formation of protein aggregates (59,60), whereas ISG15 binds to HDAC6 and p62 promoting lysosomal clearance of aggregates (61). Finally, BAG family members BAG1 and BAG3 compete for the HSP-bound polyubiquitinated substrates.…”
Section: Aggrephagymentioning
confidence: 99%
“…The main pathological hallmark of AD is the deposition of senile plaques, mainly constituted by aggregates of β-amyloid peptides in the patient's brain thought to be the cause of massive neuroinflammation. Moreover, recent studies indicated that the formation of β-amyloid plaques and neurofibrillary tangles is also caused by defects in the autophagic-lysosomal pathway, essential for the removal of misfolded and aggregated proteins or damaged organelles [19][20][21][22][23]. In particular, accumulation of β-amyloid and phosphorylated Tau proteins have been reported in the mouse models of neurological MPS including MPS IIIB and MPS IIIC diseases [18,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%